A synthesis of changes in women's empowerment in two portfolios of agricultural and livestock development projects - Galiè, Alessandra; Malapit, Hazel J.; Njiru, Nelly; Ferguson, Nathaniel; Omondi, Immaculate A.; Muchiri, Caroline; Lecoutere, Els (CGIAR GENDER Impact Platform, 2025)
The intrinsic and instrumental value of gender equality and women’s empowerment is recognized by Sustainable Development Goal (SDG) 5. Evidence on positive changes to women’s empowerment in agriculture and livestock interventions is expanding but is still relatively limited. Portfolios of projects focused on women’s empowerment through agriculture and livestock interventions can provide key insights across approaches and contexts.